Naturalizm, antynaturalizm i podstawy statystyki - Woleński, Jan (Filozofia Nauki, 2001)
Klemens Szaniawski has been dealing with many philosophical problems, but the philosophical foundations of statistics and theory of decision were his main interest. Unfortunately, he did not present his results and considerations in a synthetic monograph. One can suppose, however, that it would be an attempt to look at science from the point of view of someone who makes epistemic decisions and to regard statistical inferences as paradigmatic scientific procedures. The material concerning that subject contained in Szaniawski's published papers justifies the claim that it would be an extremely interesting synthesis. The author presents consequences for naturalism and antinaturalism that the discussions surrounding the foundations of statistics and decision theory has brought about. He often employs the results obtained by Szaniawski.